Court music of China, Japan and Korea in the 16th - 17th centuries: a comparative analysis - Guo, Linlin (Música Hodie, 2022)
Throughout history, social and economic events had a great impact on the development of culture and music as a part of it. As soon as different events have forced a cultural shift, the historical changes are considered important for music analysis. The research examines the court music of China, Japan and Korea in the 16th-17th centuries. Special attention is paid to the main characteristics, similarities and differences of music in these states. Moreover, a comparative analysis of court music in different countries was made. The purpose was to investigate the stages of the court music development, explored the historical and social events that influenced the shift in musical genres, and identified similarities and differences between musical art in different countries. The research discusses the contact between Chinese, Korean, Japanese and European cultures and its impact on the development of court music. Moreover, the research identifies similar and different characteristics found in classical musical genres such as nanxi drama (theatre) common in China, fairy tale singing popular in Japan, and ceremonial music performed in Korea. In the Far East countries, court music had features of both ceremonial and epic music associated with great orchestras with a wide variety of instruments. The musical instruments had many common features. The materials used to make the instruments and the production cycles were similar. Many instruments had analogues in other countries. The Chinese guzheng had many similar features with Japanese koto and Korean kayagum; pipa (China) is similar to biwa (Japan). Many instruments migrated from one country to another. The shakuhachi musical instrument moved from China to Japan and became very popular in this country. The music instrument was created in about 20 shapes and sizes to make distinctive sounds. Further research should consider other aspects that influenced the development of cultural values and court music in China, Japan and Korea. It is important to analyse other cultural changes and trends to understand the societal transformations, values and characteristics of the Far East countries.